How to Waste a Break: Using Portable Electronic Devices Substantially Counteracts Attention Enhancement Effects of Green Spaces. Issue 9 (November 2019) - Jiang, Bin; Schmillen, Rose; Sullivan, William C.
Overuse of portable electronic devices depletes one's attention capacity, a critical cognitive resource. Although contact with nature promotes attentional functioning, we do not know the extent to which exposure to nature and the use of electronic devices interact to promote or inhibit attentional functioning. In this study, 81 participants performed cognitive tasks and then were randomly assigned to one of four rest treatments: green settings with or without a laptop computer and barren settings with or without a laptop computer. Attention was measured three times. Analysis showed a significant effect for both setting and use of a laptop as well as a significant interaction between setting and laptop use. A further analysis controlling for time spent focused on the laptop screen produced similar results. The findings show that using an electronic device in green settings substantially counteracts the attention enhancement benefits of green spaces.